Identifications totémiques : réflexions sur la relation entre humains et entités surnaturelles chez les Salish centraux de la côte - Baptiste Gille (Journal de la Société des Américanistes)
Nowadays, many indigenous people living in the Vancouver area, on Central Coast Salish territories, can claim to have a special relationship with a supernatural entity, often a non-human animal species, a vegetal species, or an element of the landscape. The purpose of this article is to highlight the different modalities of this identification with a protective non-human being, and it takes as its starting point hesitations, difficulties, and inaccuracies that occur when one tries to define such identification. By doing so, we outline a real « totemic complex », i.e. a floating structure allowing several possible relationships with a non-human. This paper therefore proposes to reconsider the question of totemism among the Coast Salish people, and to show how it can be deepened if totemism is apprehended as a relational and flexible « complex », involving several possible relational and consistent combinations with a supernatural being.